Sign Inversion of the Spontaneous Polarization in a "de Vries"‐Type Ferroelectric Liquid Crystal. Issue 7 (25th March 2014) - Nonnenmacher, Dorothee; Lemieux, Robert P.; Osipov, Mikhail A.; Giesselmann, Frank
Abstract In contrast to common ferroelectric smectic C* liquid crystals, the siloxane‐terminated smectic mesogen E6 is characterized by an unusual temperature variation of the spontaneous polarization. The polarization starts to grow from nearly zero despite the first‐order SmA*‐SmC* transition, and increases faster than linearly over a large temperature interval while the tilt angle rapidly saturates. To study this behavior in more detail, binary mixtures of different concentrations of E6 in the achiral SmC material C8Cl, which has a similar chemical structure, were investigated. Surprisingly, all mixtures show a temperature dependent polarization sign inversion, which shifts towards the SmC*‐SmA* transition with increasing E6 concentration. For the pure E6 the inversion temperature meets the SmA*‐SmC* phase transition temperature. In a second binary mixture with E6 and a conventional material C9–2PhP we found out, that the dependence of the inversion temperature on the concentration of E6 changes qualitatively when the nanosegregation is partially destroyed. A molecular theory of the polarization sign inversion in smectics C* with strong polar intermolecular interactions is developed which enables one to explain the concentration dependence of the inversion temperature in both mixtures.